Experimental determination of mechanical properties of 3D printed PLA. Methodology for testing orthotropic materials - Zbigniew Pozorski; Jacek Andrzejewski (Polymer Testing)
The paper presents the problem of determining the material properties of 3D printed poly(lactic acid) structures. Since the material structure is created by connecting the narrow strips of the deposited material, its mechanics becomes complex. The behavior of such a material cannot be described by a simple isotropic model. For this reason, a selected set of laboratory tests necessary to identify the mechanical properties of printed poly(lactic acid) has been carried out. An elastic, orthotropic material model was assumed. The aim of the work was to describe the material accurately, taking into account different deformation conditions, but also, or perhaps even primarily, to verify the measurement methods used. For this purpose, the results of simultaneous measurements were compared using an extensometer, strain gauges, and the Digital Image Correlation technique. The measurement results clearly showed a significant error in the measurement of the modulus of elasticity for tests using a strain gauge. For the tensile tests, the recorded value of 4.2 GPa was significantly higher than the 3.5 GPa measured by the extensometer. A similar shift was observed for the bending mode, 4.0 GPa for the strain gauge measurements, and 3.5 GPa for the extensometer. Interestingly, the results for the Digital Image Correlation measurements were very consistent with the extensometer measurements, confirming the effectiveness of this technique. The tests carried out made it possible to identify reliable measurement methods and the difficulties that may occur during the implementation of some laboratory tests. In particular, the failure mechanisms observed in the shear tests carried out using the Iosipescu method are worthy of note. Finally, a set of material parameters determined for samples printed from poly(lactic acid) was presented. The obtained results can be used to design structures printed from poly(lactic acid).